Physical condition profile of prospective athletes for the Banten Province student sports education and training center: taekwondo - Amri Ikhsanul Amal; Yudha Febrianta; Anung Probo Ismoko; Imami Nugraheni; RD. Devy Citra Pratiwi; Moh. Nanang Himawan Kusuma; Sugiyan Dwi Pangestu; Nur Risma Faiza (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to determine the physical condition profiles of prospective taekwondo athletes at the Banten Province Student Sports Education and Training Center (PPLOP) in 2022 and to serve as a basis for athlete selection. The study employed a quantitative descriptive method using a survey approach. The study population and sample consisted of 10 prospective taekwondo athletes participating in the selection process, comprising 5 male athletes and 5 female athletes. The instruments used included physical fitness tests covering speed (30-meter sprint), agility (shuttle run), strength (push-ups and sit ups), power (standing broad jump and vertical jump), flexibility (sit and reach), coordination (tennis ball throw and catch), and endurance (multistage fitness test). Data were analyzed using descriptive statistics in the form of percentages. The results showed that male athletes’ speed fell into the “adequate” category, while female athletes’ speed was in the “good” category. Agility for both male and female athletes was in the “poor” category. Strength components ranged from “good” to “very good” in both groups. Lower-body explosive power, as measured by the standing broad jump, was in the “poor” to “very poor” categories, while the vertical jump was in the “adequate” category. The flexibility of both male and female athletes is rated as very good. The coordination of both groups is rated as very poor. Meanwhile, the cardiovascular endurance of both male and female athletes is rated as good. Overall, strength, flexibility, and endurance are the most prominent components, while coordination, agility, and explosive power still need improvement.